Envisioning the incorporation of Generative Artificial Intelligence into future product design education: Insights from practitioners, educators, and students - Gao, Weiyue; Mei, Yihan; Duh, Henry; Zhou, Zhibin (The Design journal, 2025)
The advancement of Generative Artificial Intelligence (GenAI) has introduced diverse opportunities and challenges in product design, demanding a corresponding evolution in design education. This study investigated GenAI's roles in product design and its implications for design education through semi-structured interviews with 24 participants, comprising practitioners, educators, and students, who had hands-on experience leveraging GenAI in design. Through thematic analysis, we identified critical functions of GenAI in product design, including generating inspiration, exploring potential solutions, conducting prototyping, performing evaluations, finalizing detailed outputs, and serving as design materials, presenting both opportunities and challenges. Moreover, fully incorporating GenAI in product design requires adaptation in educational initiatives, including capability development, curriculum content, and assessment methods. This study provides insights from a multi-stakeholder perspective, revealing the roles of GenAI in product design and advancing educational curricula to prepare the next-generation designers to be proficient in effectively leveraging GenAI for innovation.